Initial values of pores’ pressure and stress in the problems for soil consolidation - Dasibekov, Azhibek; Abzhapbarov, Azimkhan; Ashirbayev, Nurgali; Shomanbayeva, Manat (Ye.A.Buketov Karaganda State University Publishing house, 2019)
According to the basic model of V. Florin a method was developed for determining the initial excess pore pressure p0 at all points of the soil mass. Here the sum of the main stresses in the skeleton of the soil was found. Moreover, the additional pressure due to the application of external load, with an instant consolidation of the soil goes to zero. As a design scheme, a two-phase soil cylinder compaction with the radius r, the height h with a permeable bottom and walls is assumed. A uniformly distributed load with intensity q is applied on some upper part a < R of the cylinder area. In connection with the symmetry of the problem under investigation with respect to z axis, it is investigated in the cylindrical coordinates. On the basis of this result, the solution of the problem for the concentrated force is determined.
Қысымның кеуек қуысындағы бастапқы шарты және кернеудiң топырақ консолидациясындағы есебi
Начальные значения порового давления и напряжений в задачах консолидации грунтов
Keywords: pore pressure; stress; consolidation; soil; compaction; porosity